Direct anterior and direct lateral approach in patients with femoral neck fractures receiving a total hip arthroplasty: a randomized controlled trial - John Magne Hoseth; Tommy Frøseth Aae; Øystein Bjerkestrand Lian; Tor Åge Myklebust; Otto Schnell Husby (Acta Orthopaedica)
Background and purpose: The optimal approach to the hip joint in patients with displaced femoral neck fractures (dFNF) receiving a total hip arthroplasty (THA) remains controversial. We compared the direct lateral approach (DLA) with the direct anterior approach (DAA) primarily on Timed Up and Go (TUG), and secondarily on the Forgotten Joint Score (FJS), the Oxford Hip Score (OHS), EQ5D-5L, and the EQ5D-VAS. Methods: Between 2018 and 2023, we conducted a randomized controlled trial including elderly patients with dFNFs treated with THA. The primary outcome was the difference in TUG at 6 weeks postoperatively. Key secondary outcomes were TUG at 2, 12, and at 52 weeks postoperatively, and FJS, OHS, EQ5D-5L, and EQ5D-VAS at 2, 6, 12, and at 52 weeks postoperatively. Results: 130 patients with a mean age of 78.6 (standard deviation 1.2) were allocated to DAA (n = 64) or DLA (n = 66). There was no statistically significant difference in TUG times at 6 weeks postoperatively between the DAA and the DLA, 16.0 s (95% confidence interval [CI] 13.2–18.7) vs 17.8 s (CI 15.1–20.4), estimated mean difference –1.8 s (CI –5.7 to 2.0). However, patients who underwent DAA had a significantly higher FJS at 2, 6, and 12 weeks. Conclusion: Among elderly patients with dFNF we found no difference between DAA or DLA regarding crude mobility as demonstrated with the TUG test, but patients treated with DAA showed better outcomes in the FJS in the early post-fracture period though not at 52 weeks.